Synthesis, bioactivity evaluation and computational studies of bisindolylmethane and flavone derivatives / Syahrul Imran Abu Bakar - Abu Bakar, Syahrul Imran (2016)
Bisindolylmethane and flavone are well-known natural product scaffolds having important pharmacophores and they have gained tremendous interest owing to the irremarkable potency and activity profile towards various target diseases. In this study novel bisindolylmethanes and flavones were synthesized to identify potential inhibitorsfor bacterial infection, cancer, and diabetes. One hundred twenty-nine (129)bisindolylmethane derivatives (Schiff base, thiourea, sulfonamide, and hydrazone) and43 flavone derivatives (hydrazone and ether) were synthesized, evaluated for various invitro bioactivities, and analyzed through computational studies to identify possible inhibition mechanisms. Antibacterial activity of bisindolylmethane Schiff bases showedthat most compounds moderately inhibit Salmonella typhi, S. paratyphi A and S.paratyphi B bacterial strains. The results also reveals that compounds having halides and nitro substituents showed best antibacterial activity. Bisindolylmethane thioureas and sulfonamides were tested for carbonic anhydrase II inhibition activity. Molecular docking results suggest that nitro substituent at para position interacts well with Zn2+ion and interferes with the Zn-OH-Thrl99-Glul06 hydrogen bond network. Bisindolehydrazone in this study were synthesized through a three-step reaction. /^-Glucuronidase inhibitory property of some derivatives were found to be very potent (0.1-83.5 //M).Docking studies showed that active compounds should have two or more hydroxylgroups substituted on carbon adjacent to each other for good interactions to take place. Hydroxyl group at meta position of 269 was found to interact with important amino acids Glu450 and Glu540. With regards to flavone hydrazones and a-glucosidaseinhibitory activity, thirty derivatives (288-317) were found to be active (0.7-30.7 juM).Compound 288 (0.7 ± 0.2 juM) was the most active compound in the series. QSAR model developed using Discovery Studio (DS) 2.5 had successfully predicted the pICso-Molecular docking on a-glucosidase was able to identify possible binding modes responsible for the inhibitory activity. Benzohydrazone linkage enhances rotatabilityand allows iV-benzylidene moiety to interact with residues like Glu276, His348, andAsp349. In the final part of this thesis, 155 synthesized derivatives consisting of bisindolylmethanes (anilines, Schiff bases, thioureas and sulfonamides) and flavones(hydrazones and ethers) were evaluated for their antiproliferative activity against lung, breast, colon, nasopharyngeal, and endometrial cancer cell lines followed by moleculardocking studies. Docking results suggest that bisindolylmethane thiourea andsulfonamide adopt different inhibition mechanisms. Thiourea derivative 191 was ableto fit in the SI' hydrophobic pocket of MMP-2 protein, while sulfonamide 224, whichwas too bulky for MMP-2 protein, was able to fit into DDX3 protein. Molecular dockingfor Schiff base and thiourea derivatives of bisindolylmethane suggest that they inhibit through the same mechanism by targeting HER2 protein. Schiff base and thiourea interact with residues in the phosphate binding pocket and also hinge region of HER2protein. In general, the synthesized compounds represent potential leads for future drug discovery. In this study, efficient methodologies for synthesis of novel bisindolylmethanes /and flavone were developed. Biological properties of the derivatives were evaluated experimentally and rationalized through computational analysis, providing important information on vital structural features. Integrating computational analysis in drug design is a suitable approach towards obtaining drug candidates of better potency.